2008
DOI: 10.2174/187153008784534330
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine in Treatment of Metabolic Syndrome

Abstract: In management of metabolic syndrome, the traditional Chinese medicine (TCM) is an excellent representative in alternative and complementary medicines with a complete theory system and substantial herb remedies. In this article, basic principle of TCM is introduced and 22 traditional Chinese herbs are reviewed for their potential activities in the treatment of metabolic syndrome. Three herbs, ginseng, rhizoma coptidis (berberine, the major active compound) and bitter melon, were discussed in detail on their the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
225
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(229 citation statements)
references
References 154 publications
2
225
0
2
Order By: Relevance
“…Extracts and natural products derived from edible plants, such as Momordica charantia, Punica granatum, Psidium guajava , and Lycium chinensis have drawn more and more attention because of their safety profile and for the significant anti-diabetic effects that have been observed in previous studies [811]. Natural plant remedies from readily available edible plants have great potential for the prevention and treatment of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts and natural products derived from edible plants, such as Momordica charantia, Punica granatum, Psidium guajava , and Lycium chinensis have drawn more and more attention because of their safety profile and for the significant anti-diabetic effects that have been observed in previous studies [811]. Natural plant remedies from readily available edible plants have great potential for the prevention and treatment of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese medicine is an excellent system in complementary and alternative medicine. It holds great and unique potential in the management of metabolic syndrome, especially in the control of glucose and lipid metabolism [2].…”
Section: Introductionmentioning
confidence: 99%
“…Further molecular and clinical studies are necessary to elucidate the numerous bioactive substances in the ginseng berry that contribute to public health. Republic of Korea; Tel: +82 31 280 5975; Beauty Food Research Institute, R&D Center, AmorePacific Corporation, Republic of Korea; Tel: +82 31 280 5601; Page 2 of 8 It has been reported that ginsenosides are the most effective agents in ginseng in the treatment and prevention of cancer and the regulation of blood glucose and blood pressure [14]. Ginsenosides are divided into three major groups based on the triterpene aglycones panaxadiol, panaxytriol, and olenolic acid derivatives [15].…”
mentioning
confidence: 99%
“…It has been reported that ginsenosides are the most effective agents in ginseng in the treatment and prevention of cancer and the regulation of blood glucose and blood pressure [14]. Ginsenosides are divided into three major groups based on the triterpene aglycones panaxadiol, panaxytriol, and olenolic acid derivatives [15].…”
mentioning
confidence: 99%